Development of a Circular Supply Chain Model in the Retail Industry to Minimize Waste and Maximize Resource Recovery - Hedi Pandowo (Journal of Social Science and Humanities, 2026)
The Indonesian retail industry generates approximately 69.9 million tons of waste per year with a recycling rate of merely 6.5–10%, exposing deep inefficiencies in the prevailing linear "take-make-dispose" supply chain model. This study develops and validates a comprehensive Circular Supply Chain (CSC) model specifically designed for the retail sector, with the dual objectives of minimizing waste and maximizing resource recovery. Employing a sequential mixed-methods design that combines qualitative case studies across 15 retail companies with Mixed-Integer Linear Programming (MILP) optimization and Multi-Criteria Decision Making (Fuzzy DEMATEL-ANP-TOPSIS) analysis, the study systematically constructs and evaluates a five-component model encompassing a reverse logistics network, a product life extension strategy, a material recovery system, a supplier collaboration framework, and an integrated digital platform. A 12-month pilot implementation at three retail locations achieved a 45% reduction in total waste (from 6,900 to 3,795 tons/year), an increase in the resource recovery rate from 18% to 71%, and a decrease in waste-to-landfill from 82% to 23%. Financial analysis confirms strong economic viability, with a Net Present Value (NPV) of IDR 24.6 billion, an Internal Rate of Return (IRR) of 28%, and a payback period of 2.8 years. Life Cycle Assessment (LCA) using the ReCiPe 2016 method indicates a 48% reduction in carbon footprint and a 3.2-fold improvement in eco-efficiency. The model is robust to demand variations of ±20% and yields significant economies of scale, contributing measurably to Sustainable Development Goals 8, 12, and 13.